Processus cognitifs de base dans l’acquisition des langues - Gaonac’h, Daniel (My University, 1996)
Several tests with forecasting ambitions make use of performances in some elementary verbal tasks (lexical identification, immediate memory...) as a criterion of the future success in complex verbal activities (comprehension or production), as well in first as in second language. The present paper investigates the theoretical and empirical foundations of the underlying reasoning. They are mainly concerned, in the second language domain, by the degree in which some basical processes are automatized, and by the efficiency of the phonological representations formed in working memory. This analysis, from a didactical point of view, brings the question of the weighting of automatisms, and of the articulation of implicit and explicit processes in foreign languages acquisition.